Properties of Cryptocurrency as Antifiduciary Money as a Tool for Measuring Public Confidence in Power - O. A. Antoncheva; T. E. Apanasenko (Управленческое консультирование)
The use of the cryptocurrency share indicator in the total money supply as a tool for measuring public confidence in authority, allowing you to conduct an objective analysis using economic, financial indicators in order to give them a sociological assessment and develop recommendations for creating confidence management technologies. Cryptocurrency properties as antifiduciary money are considered. It is proved why an increase in the share of cryptocurrency in the money supply can be considered as a sign of a decrease in public confidence in the state. The prospects of statistics that allow tracking the dynamics of the cryptocurrency share in the money supply are analyzed. The advantages of the proposed confidence measurement tool compared to sociological survey, sociological experiment and introduction of indirect institutional indicators are demonstrated. Properties of Cryptocurrency as Antifiduciary Money as a Tool for Measuring Public Confidence in Power